8. Port of Spain (Trinidad) - Custom houses - (:unkn) unknown (My University, 2011)
The postcard shows the Port of Spain harbour and South Quay.
Colour: Sepia; Style: Landscape; Other: Unbordered, Divided
Keywords: Street-railroads--Trinidad and Tobago; Postcards; Customhouses--Trinidad and Tobago; Harbors--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Railroad tracks; Trinidad and Tobago